2016
DOI: 10.1371/journal.pone.0167567
|View full text |Cite
|
Sign up to set email alerts
|

A New Efficient Method for Detecting Phase Singularity in Cardiac Fibrillation

Abstract: BackgroundThe point of phase singularity (PS) is considered to represent a spiral wave core or a rotor in cardiac fibrillation. Computational efficiency is important for detection of PS in clinical electrophysiology. We developed a novel algorithm for highly efficient and robust detection of PS.MethodsIn contrast to the conventional method, which calculates PS based on the line integral of the phase around a PS point equal to ±2π (the Iyer-Gray method), the proposed algorithm (the location-centric method) look… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…A PS trajectory map on the atrial surface was also generated. The PS was defined at the point where the phase was undetermined 20,21 . We sampled the 6-s data for a single PS calculation in our previous study 7 .…”
Section: Definition Of Base Electrophysiological Parameters Of Fibrotmentioning
confidence: 99%
See 1 more Smart Citation
“…A PS trajectory map on the atrial surface was also generated. The PS was defined at the point where the phase was undetermined 20,21 . We sampled the 6-s data for a single PS calculation in our previous study 7 .…”
Section: Definition Of Base Electrophysiological Parameters Of Fibrotmentioning
confidence: 99%
“…We sampled the 6-s data for a single PS calculation in our previous study 7 . We then used the location-centric method 21 that we previously developed for identifying the phase singularity points with a high computational speed and accuracy. We previously validated our method by comparing it with the Iyer-Gray method.…”
Section: Definition Of Base Electrophysiological Parameters Of Fibrotmentioning
confidence: 99%
“…One of reasons why these interpretations of stimulation effect have not been integrated until today is the difficulty in objectively identifying the SW and its trajectory in the complex transition of excitation pattern that is observed just after stimulation. In 1998, Gray and colleagues (13,33) revealed that a complex SW can be analyzed by defining the center of the SW as a phase singularity (PS) in the phase map. However, quantitative tracking of the center of the SW is not available even by using the mathematical definition of PS (13,33).…”
Section: Introductionmentioning
confidence: 99%
“…In 1998, Gray and colleagues (13,33) revealed that a complex SW can be analyzed by defining the center of the SW as a phase singularity (PS) in the phase map. However, quantitative tracking of the center of the SW is not available even by using the mathematical definition of PS (13,33). Therefore, the quantitative analysis of the interaction process of shock-induced PSs and the original PS has not been reported and the action mechanism of stimulation has not yet been fully clarified experimentally from the viewpoint of PS interactions.…”
Section: Introductionmentioning
confidence: 99%
“…In the phase maps, rotors are represented by phase singularity (PS) points [5] that are surrounded by regions in all possible phases of electrical activation [6,7].…”
Section: Introductionmentioning
confidence: 99%